Measurement of Company Performance and Market Value as Measured by Family Involvement of Founders in Family Business in Indonesia - Wijaya, John Henry; Fatihat, Gita Genia; Utami, Eristy Minda (Technium Business and Management, 2026)
Family businesses dominate Indonesia’s economic landscape, contributing over 80% of GDP and 96% of employment; yet the extent to which founding family involvement translates into superior firm performance and market value remains empirically contested. This study examines the relationship between founding family involvement and two performance dimensions — financial performance, proxied by Return on Investment (ROI), and market value, proxied by Tobin’s Q, while controlling for firm size, firm age, and investment risk. Using an unbalanced panel dataset of 40 family firms listed on the Indonesia Stock Exchange (IDX) over the 2021–2024 period (157 observations), this study employs panel data regression with a Random Effects Model (REM), selected through the Chow, Hausman, and Lagrange Multiplier (Breusch-Pagan) tests. The results reveal that ROI has no significant effect on Tobin’s Q (p = 0.483), suggesting that internal profitability does not automatically translate into higher market valuation. Firm size exerts a significant negative effect on Tobin’s Q (p = 0.000), consistent with agency cost theory, as larger firms tend to face greater bureaucratic inefficiencies and overinvestment risks. Investment risk significantly and negatively affects Tobin’s Q (p = 0.000), aligning with agency theory arguments that higher risk raises the cost of capital and depresses investor confidence. Firm age has no significant effect on market value (p = 0.404), indicating that industry dynamics and strategic focus outweigh organizational longevity in driving market valuation. These findings contribute to the family business literature by highlighting a systematic divergence between internal performance metrics and external market perceptions in the Indonesian context, and suggest that founding family involvement per se is insufficient to guarantee market value creation without complementary professional governance mechanisms.